2021
DOI: 10.1016/j.isci.2021.103074
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic ERK1/2 signaling dynamics distinguishes necroptosis from apoptosis

Abstract: ERK1/2 involvement in cell death remains unclear, although many studies have demonstrated the importance of ERK1/2 dynamics in determining cellular responses. To untangle how ERK1/2 contributes to two cell death programs, we investigated ERK1/2 signaling dynamics during hFasL-induced apoptosis and TNF-induced necroptosis in L929 cells. We observed that ERK1/2 inhibition sensitizes cells to apoptosis while delaying necroptosis. By monitoring ERK1/2 activity by live-cell imaging using an improved ERK1/2 biosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…We ask to what extent signaling and morphology changes contribute to heterogeneous and dynamic chemotactic movement. We found that cells also exhibit fluctuations in ERK and Akt signaling, similar to what were reported in previous studies, driving cell behaviors like cell division, death, and migration (12,13,(16)(17)(18)(19)(20). Single-cell signaling responses varied from strong fluctuations of both ERK and Akt to undetectable fluctuations (Fig.…”
Section: A-ii)supporting
confidence: 87%
“…We ask to what extent signaling and morphology changes contribute to heterogeneous and dynamic chemotactic movement. We found that cells also exhibit fluctuations in ERK and Akt signaling, similar to what were reported in previous studies, driving cell behaviors like cell division, death, and migration (12,13,(16)(17)(18)(19)(20). Single-cell signaling responses varied from strong fluctuations of both ERK and Akt to undetectable fluctuations (Fig.…”
Section: A-ii)supporting
confidence: 87%
“…The Erk1/2 pathway was reported to play a critical role in determining cellular responses, such as proliferation and differentiation, and phosphorylated Erk1/2 was involved in tumor progression. As a downstream regulator of the Erk1/2 pathway, COX-2 plays an important role in the genesis and development of cancer. As downstream genes regulated by RARβ, the protein expressions of the total Erk1/2 (t-Erk1/2), phosphorylated Erk1/2 (p-Erk1/2), and COX-2 in H4IIE cells were measured. In the absence of RA (an RARβ agonist) and U0126 (an Erk1/2 antagonist), there was no significant modification in the total Erk1/2 protein; however, the expression of p-Erk1/2 was changed (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…This difference in inhibition kinetics could reflect differences in conformational flexibility and/or steric hindrance that reduce accessibility of the sensor backbone to phosphatases. 64,65 We also found that the JF549SNAP/JF646Halo combination offered a 2-fold higher contrast than the JF549Halo/ JF646SNAP combination, suggesting that in at least some systems the labeling efficiency of the Halo domains is higher than that of the SNAP domains.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…In this paper, we evaluated this combination by replacing the FP moieties in existing sensors with SNAP and Halo domains (Figure 1) and examining the performance of the modified sensors after live-cell staining with a range of organic dyes. 63 In particular, we found that we could readily produce chemigenetic variants of AKAR3EV, 64 a sensor for protein kinase A (PKA), EKAR4.0, 65 an extracellular signal-regulated kinase (ERK) activity reporter, and Yellow Cameleon 3.6 (YC), a sensor for Ca 2+ . 66 The resulting constructs can deliver similar signal-to-noise ratios compared to their CFP/YFPbased ancestors, yet permit convenient spectral tunability that readily allows the creation of color-shifted variants.…”
mentioning
confidence: 99%